Matrix metalloproteinases and their tissue inhibitors as upcoming biomarker signatures of connective tissue diseases-related interstitial lung disease: towards an earlier and accurate diagnosis - Verónica Pulito-Cueto; Belén Atienza-Mateo; Joao C. Batista-Liz; María Sebastián Mora-Gil; Víctor M. Mora-Cuesta; David Iturbe-Fernández; Sheila Izquierdo Cuervo; Carolina Aguirre Portilla; Ricardo Blanco; Raquel López-Mejías (Molecular Medicine)
Abstract Background Lack of understanding of interstitial lung disease (ILD) associated with systemic sclerosis (SSc) and rheumatoid arthritis (RA) hinders the early and accurate identification of these devastating diseases. Current clinical tools limitations highlight the need to complement them with accessible and non-invasive methods. Accordingly, we focused on identifying useful matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) as new biomarkers with clinical value in the diagnosis and prognosis of RA-ILD+ and SSc-ILD+. Methods Peripheral blood was collected from patients with RA-ILD+ (n = 49) and SSc-ILD+ (n = 38); as well as with RA-ILD- (n = 25), SSc-ILD- (n = 20) and idiopathic pulmonary fibrosis (IPF) (n = 39). MMP-1, MMP-2, MMP-3, MMP-7, MMP-9, MMP-10, MMP-12, TIMP-1, and TIMP-2 serum levels were measured using xMAP Technology. Results Concerning early connective tissue disease (CTD)-ILD+ diagnosis, increased MMP-7, MMP-9, MMP-10, and MMP-12 levels were found in RA-ILD+ and SSc-ILD+ patients in relation to RA-ILD- and SSc-ILD- patients, respectively. RA-ILD+ patients showed higher MMP-2 levels and lower TIMP-1 levels than RA-ILD- patients. Interestingly, a reliable utility for identifying ILD in CTD was confirmed for the MMP-2, MMP-7, MMP-9, MMP-10, MMP-12, and TIMP-1 combination in RA and MMP-7, MMP-9, MMP-10, and MMP-12 combinatorial signature in SSc. Regarding accurate CTD-ILD+ diagnosis, RA-ILD+ and SSc-ILD+ patients showed lower MMP-7 and MMP-10 levels than IPF patients. Lower MMP-9 and TIMP-1 levels and higher MMP-3 levels were found in RA-ILD+ compared to IPF. Remarkably, effectively better differentiation between CTD-ILD+ and IPF was confirmed for a 5-biomarker signature consisting of MMP-3, MMP-7, MMP-9, MMP-10, and TIMP-1 in RA as well as for the MMP-7 and MMP-10 combination in SSc. Finally, in RA-ILD+ patients, higher MMP-10 levels were associated with worse pulmonary function, increased MMP-2 levels were related to the treatment with conventional synthetic disease-modifying anti-rheumatic drugs, and decreased TIMP-1 levels were linked with positivity rheumatoid factor status. Conclusions MMPs and TIMPs form combinatorial biomarker signatures with clinical value for non-invasive, early, and accurate diagnosis of RA-ILD+ and SSc-ILD+, constituting promising screening tools in clinical practice.